Phase transformation on spark plasma sintered dense polycarbosilane-derived SiC without additive. (15th January 2018) - Lee, Yoonjoo; Lee, Ji Hwoan; Shin, Dong-Geun; Noviyanto, Alfian; Lee, Heyon-Myong; Nishimura, Toshiyuki; Jang, Byung-Koog; Kwon, Woo-Teck; Kim, Younghee; Kim, Sukyoung; Han, Young-Hwan
Abstract: SiC was sintered by spark plasma sintering (SPS) using polycarbosilane (PCS), and the effects of pressure on the sintering behavior of SiC during SPS were investigated. The pressure conditions were set as 40 and 80 MPa, and pyrolyzed PCS was used to induce reactive sintering during heat treatment such as pyrolysis, crystallization, and crystal growth. According to the results, a high pressure accelerated the reactions in samples and resulted in a high-density body consisting of small-sized grains; however, it induced a phase transition to the α phase, which is stable at high temperatures.